Kompleksitas Penyelenggaraan Layanan Pendidikan Anak Usia Dini (PAUD) dalam Perspektif Standar Nasional PAUD - Mahmudin, Dikki Zulfikar; Wiyani, Novan Ardy (QUALITY, 2023)
The Complexity of Early Childhood Education (PAUD) Service Delivery in the Perspective of the National PAUD Standards. This study aims to explore the challenges and actions taken in implementing PAUD services in accordance with national standards at PAUD Waluyo Jati Gumelem Kulon, Susukan District, Banjarnegara Regency. The language is objective, formal, and unbiased. The text is free from grammatical, spelling, and punctuation errors. It is case study research that utilized interviews, observations, and documentation as data collection methods. The Miles and Huberman model data analysis technique was employed, including data reduction, data display, and verification stages. Abbreviations and technical terms are clearly defined upon initial use. The outcomes indicated that PAUD Waluyo Jati encountered issues in all standards during service implementation. STPPA experienced difficulties utilizing tools to evaluate the growth and development of young children. Compiling a curriculum that takes into account institutional peculiarities presented challenges in the content standard. In terms of the process standard, obstacles arose in preparing RPPM and RPPH. In the assessment standard, issues have arisen regarding the execution of assessments that do not align with the assessment tool. In the education personnel standard, difficulties stem from the compliance with academic qualifications required of teachers. In the facilities and infrastructure standard, limitations are observed in terms of available restrooms and workspace. Financial standards present challenges in raising funds to provide PAUD services, while management practices at PAUD Waluyo Jati suffer from inadequate documentation of program implementation. In light of these difficulties, PAUD Waluyo Jati should strive for continuous improvement in meeting national PAUD standards by preparing activity programmes that comply with these standards. Penelitian ini bertujuan mendeskripsikan kesulitan dan upaya yang dihadapi pada penyelenggaraan layanan PAUD dalam perspektif standar nasional PAUD di PAUD Waluyo Jati Gumelem Kulon Kecamatan Susukan Kabupaten Banjarnegara. Penelitian ini merupakan penelitian studi kasus. Data dikumpulkan melalui wawancara, observasi dan dokumentasi. Kemudian dianalisis menggunakan teknik analisis data model Miles dan Huberman yang terdiri dari tahap reduksi data, display data dan verifikasi. Hasil penelitian menunjukan bahwa pada penyelenggaraan layanan PAUD Waluyo Jati mengalami kesulitan dalam setiap standarnya.Pada STPPA ditemukan kesulitan dalam hal penggunaan instrumen untuk melakukan assesment terhadap tumbuh-kembang anak usia dini. Pada standar isi ditemukan kesulitan dalam menyusun kurikulum yang sesuai dengan kekhasan lembaga. Pada standar proses ditemukan kesulitan dalam penyusunan RPPM dan RPPH. Pada standar penilaian ditemui kesulitan terkait dengan pelaksanaan penilaian yang belum sesuai dengan instrumen penilaian. Pada standar pendidik dan tenaga kependidikan ditemui kesulitan terkait dengan pemenuhan kualifikasi akademik guru. Pada standar sarana dan prasarana ditemui kesulitan berupa keterbatasan toilet dan ruang kerja. Pada standar pembiayaan ditemui kesulitan dalam hal penggalangan dana untuk pembiayaan penyelenggaraan layanan PAUD. Pada standar pengelolaan ditemui kesulitan pihak guru PAUD Waluyo Jati belum mampu mendokumentasikan setiap pelaksanaan program dengan baik.Berdasarkan kesulitan-kesulitan di atas maka sebaiknya PAUD Waluyo Jati melakukan upaya perbaikan secara berkelanjutan dalam pemenuhan standar nasional PAUD dengan menyusun program kegiatan PAUD yang sesuai dengan standar nasional PAUD.